ORGANIC COMPOSITION OF EYE LENS OF CATLA CATLA AT DIFFERENT STAGES OF GROWTH - Goswami, A K (Indian Journal of Fisheries, 2011)
Some organic components of eye lens of fish, Catla catla, at three stagesof growth have been studied. Stage I and II contains 19 aminoacids, whilestage III contains 20. The quantity of glutamic acid has been found to be themaximum and tryptophan to be the minimum in alt the three stages. The valueof ascorbic acid in eye lens decreases with growth, but the nitrogen contentincreases gradually.